Ur gonna have to pick an equation and solve for a variable.
2x - 2y = 6
2x = 2y + 6 ...divide everything by 2 because u want x by itself
x = y + 3
now we sub y + 3 in for x in the other equation
14x - 2y = 78
14(y + 3) - 2y = 78...distribute thru the parenthesis
14y + 42 - 2y = 78...subtract 42 from both sides, cancelling the 42 on the left
-42 -42
-----------------------
14y - 2y = 36 ...simplify
12y = 36...divide by 12 on both sides, cancelling out the 12 on the left
y = 36/12
y = 3
now , we already know that x = y + 3...and we know y = 3...so sub in 3 for y and solve for x
x = y + 3
x = 3 + 3
x = 6
solution is (6,3)
it is always a good idea to check ur answer by subbing it into one or both of the equations to see if it is correct
2x - 2y = 6......(6,3)...x = 6 and y = 3
2(6) - 2(3) = 6
12 - 6 = 6
6 = 6 (correct)
so yes, ur solution is (6,3)
Answer:
x = 1/2 or 0.5
Step-by-step explanation:
3x - 4 = x +5 (1) subtract x
2x - 4 = 5 (2) subtract 5
2x + 1 (3) divide by 2
x = 1/2 or 0.5
There’s are ratio which would be 8/10. 12/x should equally 8/10. So it would be 14 tiles long.
Answer:
y=(7)^x represents the exponential growth
Sense the two triangles are congruent you would use CPCTC.